1995
DOI: 10.1007/bf00232919
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of plantlets from petiole callus of wild viola (Viola patrinii DC.)

Abstract: Plantlets were regenerated from 5-year subcultured compact callus derived from petiole tissues of wild viola (Viola patrinii DC.) but not from 5-year subcultured friable callus. Regeneration occurred most efficiently on medium that contained two-fold diluted basal salts of Murashige and Skoog's (MS) medium, 5 × 10(-6) M 1-naphthaleneacetic acid and 10(-6) M kinetin. The effect of dilution of MS basal salts could also be achieved solely by two-fold dilution of the potassium dihydrogen phosphate in the mixture.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Petiole explants and half-strength MS medium (2.8 mg/l) were more productive in efficient shoot organogenesis in Viola caspia subsp. sylvestrioides, in agreement with previously re-ported results on Viola wittrockiana (Sato et al, 1995), where it was shown that multiple shoot organogenesis could be achieved from petiole callus using a halfstrength MS medium supplemented with BAP in combination with NAA. The number of regenerated shoots formed on leaf explants was greater than the number of shoots obtained on petiole explants (approx.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Petiole explants and half-strength MS medium (2.8 mg/l) were more productive in efficient shoot organogenesis in Viola caspia subsp. sylvestrioides, in agreement with previously re-ported results on Viola wittrockiana (Sato et al, 1995), where it was shown that multiple shoot organogenesis could be achieved from petiole callus using a halfstrength MS medium supplemented with BAP in combination with NAA. The number of regenerated shoots formed on leaf explants was greater than the number of shoots obtained on petiole explants (approx.…”
Section: Discussionsupporting
confidence: 92%
“…Depending on the genotype of plants and the type of explants, TDZ induces different regeneration responses (Passey et al, 2003). TDZ, with a high cytokinin-like activity (Huetteman and Preece, 1993), is widely used to promote shoot proliferation in many plant species, including the members of Violaceae (Sato et al, 1995;Slazak et al, 2015;Żabicki et al, 2019). The study by Slazak et al (2015) revealed that TDZ had the potential to induce direct and indirect organogenesis in leaf and petiole explants of Viola uliginosa Besser (Slazak et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The best results were achieved on media with half-strength MS mineral salts containing full-strength Na-FeEDTA and vitamins. These findings are in agreement with those of Sato et al (1995) and Mokhtari et al (2016), who revealed that dilution of basal salts of MS medium was important for successful shoot induction and plantlet regeneration of other violas and pansies.…”
Section: In Vitro Plant Propagation and Acclimatizationsupporting
confidence: 92%
“…This is in accordance with results obtained for not only seedling explants, but also other ex vitro or in vitro grown shoots of different Viola spp. (Sato et al 1995;Wang and Bao 2007;Vishwakarma et al 2013;Antonić et al 2017). Seedling explants (petiole, leaf or root segments) as an initial source of primary explants for establishing a protocol for Viola spp.…”
Section: In Vitro Plant Propagation and Acclimatizationmentioning
confidence: 99%
See 1 more Smart Citation